Sazonal horizontal distribution of Erythmelus tingitiphagus (Hymenoptera: Mymaridae) in the rubber tree plantation - Santos, Rodrigo Souza (2009)
The egg parasitoid Erythmelus tingitiphagus (Soares) is one of the main natural enemies of lace bug Leptopharsa heveae Drake & Poor (Hemiptera: Tingidae), together with the green lacewings and the fungus Sporothrix insectorum (Hoog e Evans). Studies about insect-pest distribution and their natural enemies in rubber tree are scarce. The objective of this research was to verify the sazonal horizontal distribution and population fluctuation of the parasitoid E. tingitiphagus in commercial blocks of rubber tree of the clones RRIM 600, PR 255, PB 217, PB 235 and GT 1, from october of 2005 to february of 2006, period of occurrence of L. heveae in the studied area. The samplings were performed in the North, South, East and West quadrants of five blocks, Ripe leaves of the inferior third of the canopy of five marked trees, from the edge towards the interior of the blocks, were collected. The leaves were taken to the laboratory, washed in sodium hypochlorite solution (1.5%), rinsed and dried under absorbent paper. The petioles of each leaflet were inserted in plastic tubes containing water, sealed, conditioned in identified plastic bags (12 x 30 cm), filled with an air compressor and closed in electric stamp. The material was suspended in clothes lines in an acclimatized room at 25 ± 1 ºC and 12 hours of photoperiod. After five days, the bags and leaflets were observed under stereoscopic microscope, to verify the parasitoids emergence. The data were normalized and submitted to the variance analysis (ANOVA) and their averages were compared by the Tukey’s test (5%). An equal distribution of the parasitoid was verified, varying on average for the five clones from 2.59 (South) to 2.82 (West). There was a tendency of the parasitoid to concentrate inside the rubber tree blocks. The clones that presented the largest and smallest parasitoids number were PR 255 and PB 235, respectively. In the studied areas, the population peaks of the parasitoid occurred in November for all the clones, except for PR 255, which had its peak in December.